Metodologias de síntese e modificações estruturais em meso-Tetraarilporfirinas - Momo, Patrícia Betoni (2016)
In this thesis we describe studies towards the synthesis of porphyrins aiming the optimization of literature protocols leading to more environmental friendly approaches. Also, structural modifications and photophysical evaluations in meso-tetraarylporphyrins were studied, especially in mesotetra(thien-2-yl) porphyrins. Classical synthetic methods for porphyrins involve the use of high temperatures, toxic solvents, high dilution, and often low yields. In view of this, we decided to explore the methodology described by Bonar-Law in order to verify the feasibility of using aqueous environments in the synthesis of porphyrins. Some modifications were studied using sodium dodecylbenzylsulfonate (SDBS) as a critical micelle-forming instead of sodium dodecyl sulfate (SDS) as previously described, and the use of trichloroisocyanuric acid as oxidizing agent instead of 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ), and montmorillonite K-10 as catalyst instead of HCl. These were chosen in order to use reagents with less environmental impact. However, the results were not satisfactory, yielding amounts of side-products reported in the literature. Also, we have studied the synthesis of porphyrins under continuous flow conditions, since the use of this technology gives more safety and efficiency to chemical reactions. The experiments under continuous flow conditions were performed using an adaptation of Gonsalves and Lindsey methodologies. First, the synthesis of tetraphenylporphyrin (TPP) was optimized, and different flow, temperature and concentration of reagents were evaluated in order to obtain the best reaction conditions. Thus, under continuous flow conditions employing tubular reactors (adaptations Gonsalves methodology), the highest yield for mesotetraphenylporphyrin (TPP) was 31% using a concentration of 0.2 mol L-1 for the pyrrol, and benzaldehyde, a flow of 0.6 mL min-1 at 140 °C. For comparison, the same experiment performed in batch resulted in 25% yield for TPP. Moreover, streaming technology has enabled the synthesis of various meso-substituted derivatives in yields of 9% to 39% indicating good versatility of this tool. The use of solid phase reactors (Lindsey methodology adaptations) consisted of preliminary experiments should be explored in more detail and will be carried on by the research group. With regard to meso-tetra(2-thienyl)porphyrins, these exhibit unique photophysical, photochemical and electrochemical properties and have been identified as potential photosensitizers for photodynamic therapy (PDT) and solar cells (CS) applications. In view of this, we decided to study different conditions for the synthesis, structural modification and the photodynamic properties of these porphyrin derivatives. Meso-tetra(2-thienyl)porphyrin was successfully synthesized using different methodologies with improvements in the yields after experimental modifications of the literature procedures. After systematic studies, meso-tetra(thien-2-yl)porphyrin was obtained in pure form with 36% yield, using chlorobenzene as solvent, hydroxylamine hydrochloride as catalyst and nitrobenzene as oxidant. Nitration reactions were carried out using mild reaction conditions with sodium nitrite and trifluoroacetic acid. The nitrated derivatives were obtained at α-position of thiophene in 66% yield for the mono-nitro product and 59% for the tetra-nitro product. Also, the Vilsmeier-Haack reaction was studied for obtaining functionalized meso-tetra(2-thienyl)porphyrins with formyl groups. In these studies only formylations at the α-position of the thiophene ring were observed, and no formylation at the β position of the porphyrin core (common for tetraphenylporphyrins). Moreover, we obtained reaction conditions in which only mono-formylated product was formed (10%), or only the tetra-formylated product (10%), as well as experimental conditions that yielded different products (mono, di, tri and tetra -formylated). After obtaining the desired formylated product, we studied the application of mono-formylated product in Wittig reaction, Peterson olefination and condensation with 4,4-difluoro-4-bora-3a, 4adiaza-s-indacene (BODIPY ). The latter studies were only an initial exploration and still require further elaboration. Porphyrin derivatives as 2-thienyl-chlorins and 2-thieny- bacteriochlorins were obtained by cycloaddition reactions with nitrile oxide 1,3-dipole with good yields. Also, preliminary photophysical studies of these compounds were performed in order to evaluate the potential of these photosensitizers as photoactive dyes. The photophysical results indicated that the obtained compounds are good producers of oxygen, present good photo-stability and did not undergo aggregation in the studied concentration range. Therefore, the 2- thienyl-chlorins and 2-thienyl-bacteriochlorins obtained in this study showed promising characteristics for use as photosensitizers in photodynamic therapy. Finally, the new heterocycles herein obtained presented bathochromic shift of the absorption bands in the electromagnetic spectrum, since molecules having this characteristic represent high interest in chemical photosensitizers.